The influence of Leadership Styles to Improving Work Motivation of Nurses on Implement Nursing Care in Irna C of Sanglah Hospital. - M.A. Meiniyari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Quality of nursing work is strongly influenced by work motivation. Although treatment facilities are adequate, but without having a high work motivation it will be difficult to nurses to give satisfactory service, because of that head room as a leader have an important role to enhance the motivation of working nurses. The purpose of this research is to know is there any influence of leadership styles to improving work motivation of nurses on implement nursing care in Irna c of Sanglah Hospital. This research is kind of correlation study with cross sectional approach. The samples are 71 of nurses that taken with proportionate stratified random sampling. Data is collecting use the questionnaires. The results showed a tendency of leadership style that applied is participatory with the motivation of working nurses are moderate. The results of analyst by rank spearman test showed there was influence of leadership styles to improving work motivation of nurses on implement nursing care in Irna C of Sanglah Hospital, with p value = 0.015 (p < 0.05) and coefficient correlation 0.289. Based on the results of the research, it’s recommended that the head room can apply good leadership style that effective to increasing the motivation of working nurses who work in maintenance room C Sanglah Hospital, so nurses can provide the best in healthcare.